Peran Komunikasi Antar Pribadi Terhadap Orang Tua Dalam Pembentukan Karakter Anak - Nur Fitriyani Hamzah; Mochammad Mirza; Ajeng Pradesti (Institut Nalanda, 2024)
The role of interpersonal communication can also occur in a family environment, involving communication relationships between children and parents. Children need interaction with others for their growth. Despite the importance of interpersonal communication to parents and children, many parents face the challenge of establishing effective communication with their children. Factors such as generational differences, good communication styles, and pressure from the environment can be obstacles in creating a healthy communication relationship between parents and children. In this study, interpersonal communication between parents and children on shaping the character of their children in Tangerang. Using qualitative research methods, this study explores communication interactions through observation and questioning deliberate participation, incorporating symbolic theory. The results of this study are that effective interpersonal communication can help parents understand the needs and feelings of their children. A parent who understands the needs and feelings of the child will be able to provide appropriate guidance and guidance to the child.